Improvement of Student Critical Thinking Skills with the Natural Product Mini Project Laboratory Learning - Aliefman Hakim; Liliasari Liliasari; Asep Kadarohman; Yana Maolana Syah (Indonesian Journal of Chemistry, 2016)
This research aims to investigate effect of learning using natural product mini project laboratory on students’ critical thinking skills. The research was conducted on sixth semester of 59 students of chemistry and chemistry education program from one of the state universities in West Nusa Tenggara, Indonesia in 2012/2013. This research revealed class where the student learn using natural product mini project laboratory had more critical thinking skills than those using verification laboratory. The average n-gain of critical thinking skills for experiment class was 0.58 while for the control class was 0.37. The highest n-gain in the experiment class was 0.70 for “deciding on an action (selecting criteria to judge possible solutions) indicators”, while the smallest n-gain was 0.47 for “the making and judging value of judgments (balancing, weighing, and deciding) indicators. We concluded that the natural product mini project laboratory was better than verification laboratory in improving the students’ critical thinking skills.